Clinical Management of Epilepsy With Glutamic Acid Decarboxylase Antibody Positivity: The Interplay Between Immunotherapy and Anti-epileptic Drugs - Mäkelä, Kari-Matti; Hietaharju, Aki; Brander, Antti; Peltola, Jukka (Frontiers in Neurology, 2018)
Background: There is scanty guidance in the literature on the management of patients with glutamic acid decarboxylase (GAD65) antibody associated autoimmune epilepsy (GAD-epilepsy). GAD-epilepsy is a rare distinct neurological syndrome with a wide clinical spectrum. We describe six GAD-epilepsy patients with special emphasis on the treatment timing and the relationship between immunologic and anti-epileptic therapy. Methods: Six patients diagnosed with GAD-epilepsy in Tampere University Hospital who had received immunotherapy from 2013 to 2017 were retrospectively analyzed from patient records. Data about symptom onset, including antibody levels, magnetic resonance imaging (MRI), electroencephalograms, immunotherapy and anti-epileptic treatment timing and treatment responses were collected and analyzed. Kruskall-Wallis test was used in the statistical evaluation. Results: All patients were female aged 9–54 at symptom onset. Two had hypothyroidism, none had diabetes, one had migraine. Five patients had very high (> 2000 IU/ml) and one had high (52–251 IU/ml) GAD65 antibody titers. All patients presented with seizure disorders. Patients who received early initiation of immunotherapy (3–10 months) responded well to treatment; patients in whom the immunotherapy was started later (15–87 months) did not respond (p=0.0495). The first patient was seizure-free after one year of regular intravenous immunoglobulin and two antiepileptic drugs (AED). The second patient developed unilateral temporal lobe T2 signal changes in MRI; she responded well to immunotherapy, experiencing a significant reduction in seizure frequency and resolution of MRI abnormalities. However, seizures continued despite trials with several AEDs. The third patient responded well to immunoadsorption and rituximab with one AED, with lowering of GAD65 titers (from > 2000 to 300). There was a long delay in the diagnosis of GAD-epilepsy in the three patients who had developed refractory epilepsy, one with hippocampal sclerosis. They all received immunotherapy but none responded. However, AED modification or vagus nerve stimulation reduced the seizure frequency in two patients. Epilepsy surgery was ineffective. Conclusions: These results highlight the importance of early detection of GAD65 antibodies in refractory epilepsy as immunotherapy can be effective if administered in the early stages of the disease when it can prevent permanent brain tissue damage.